2022
DOI: 10.1039/d1qi00501d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a stable and inert MnII-based ZnII responsive MRI probe for molecular imaging of glucose stimulated zinc secretion (GSZS)

Abstract: A new potential Zn(II) responsive Mn(II)-based MRI CA candidate derived form pyclen-3,9-diacetate (3,9-PC2A) has been synthesized possessing a di-(2-picolyl)amine (DPA) moiety as an active arm. The PC2A-DPA ligand was found...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 45 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…The increase can be visualized by MRI experiments in vitro , and in vivo tests confirmed that GSZS could be observed in the prostate of a healthy mouse. 31 Jasanoff's group developed a Mn-based MRI CA (43, Fig. 2 ) as a sensor for intracellular calcium ions (Ca 2+ ).…”
Section: Metal Complexes In Bioimaging Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase can be visualized by MRI experiments in vitro , and in vivo tests confirmed that GSZS could be observed in the prostate of a healthy mouse. 31 Jasanoff's group developed a Mn-based MRI CA (43, Fig. 2 ) as a sensor for intracellular calcium ions (Ca 2+ ).…”
Section: Metal Complexes In Bioimaging Applicationmentioning
confidence: 99%
“…7,20,[28][29][30] The application of the metals essential for life can avoid the introduction of exogenous metals and the problems of biotoxicity and metabolism. 31,32 In recent years, a series of metal complexes-based probes have been developed with OI and MRI modalities, which can overcome the shortages of organic molecular probes and avoid the metabolic difficulty and biotoxicity of nano-sized probes. 9,16,19 More importantly, metal complexes-based probes have the potential to be used as bioimaging agents in clinic.…”
Section: Introductionmentioning
confidence: 99%
“…of the macrocycle. 41 A relatively long synthetic sequence was required in this case. Thus, the primary amine of pytren was protected as phthalimide to facilitate the introduction of tertbutyl acetate groups by alkylation.…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
“…More recently, Tircsó's group reported the synthesis of a new ligand L35 decorated with a tridentate arm at position 6 of the macrocycle. 41 A relatively long synthetic sequence was required in this case. Thus, the primary amine of pytren was protected as phthalimide to facilitate the introduction of tert -butyl acetate groups by alkylation.…”
Section: Synthesis Of Pyridine-containing 12-membered Tetraazamacrocy...mentioning
confidence: 99%
“…However, its inertness requires further improvement as [Mn(3,9-PC2A)] is readily protonated, favoring an efficient dissociation via the proton-assisted mechanism (as confirmed by the calculation of the electrostatic potential using DFT methods). However, for the H 2 3,9-PC2A derivatives recently proposed as smart imaging probes (SCAs) for detecting tissue pH sensing Zn(II) ions or for angiographic imaging (H 2 3,9-PC2A-EA, H 2 3,9-PC2A-BP and H 2 3,9-PC2A-DPA, respectively, Scheme S1) the required inertness is achieved by the attachment of ethylamine (possessing picolyl moieties for Zn(II) sensing) or biphenyl moieties; herein, we intend to eradicate the most basic protonation site of the ligand [17][18][19]. It is achieved by the replacement of one amine nitrogen in the macrocycle for an etheric oxygen atom.…”
Section: Introductionmentioning
confidence: 99%